Mengelola Perubahan Organisasional: Isu Peran Kepemimpinan Transformasional dan Organisasi Pembelajaran dalam Konteks Perubahan - Sri Dwi Ari Ambarwati (Jurnal Siasat Bisnis, 2003)
The end of twentieth century will be driven by a new set of expectation. As a result of globalization within organizational development will reshape intervention strategies through learning organization and transfor¬mational leadership model. They’re important to drive organizational change because of breathtaking changes foreseen in the business and political environment and that change requires creating a new system and then in¬stitutionalizing the new approach.This paper reviews roles of the learning organization and transformational lea¬dership in successful managing change process. This paper divided into five sections. First, importance revolution will be presented to describe step of organization growth. Second, focus on how to manage organization change. The third, describe role of the learning organization to drive change. The Fourth, describe role of transformational leadership. And whole discussion will be cloncuded in the fifth section.Keyword: revolution,learning organization , transformational leader model.